Lung auscultation as a predictor of lung lesions and bovine respiratory disease outcome in feed yard cattle - DeDonder, Keith David (Kansas State University, 2008)
Bovine respiratory disease complex (BRDC) is the most common, and costly, disease in feed yard cattle. A review of the literature shows a correlation between the diagnosis of BRDC ante-mortem and respiratory lesions at slaughter. The objectives of the studies reported here were to: 1) validate a thoracic auscultation scoring system by correlating ante-mortem lung sounds with post-mortem lung lesions and 2) evaluate thoracic auscultation and rectal temperature as diagnostic tools to predict case outcome in the feeder cattle treated for BRDC. First, a prospective cohort study involving thirty four head of cattle that had been realized from commercial cattle feeding operations were used to validate the use of a lung auscultation scoring system to identify cattle suffering from BRDC. Ante-mortem auscultation scores were compared to post-mortem lung lesions evaluated using a previously described scoring system. There was a positive correlation (P < .0001) between ante-mortem lung auscultation scores and post-mortem lung lesion scores in the population of feeder cattle that were tested. Subsequently, a retrospective cohort study was conducted using data obtained from three commercial feed yards. Cattle enrolled in the study (n = 4,341 head) were treated for BRDC between January 2007 to October 2007 by trained feed yard personnel. Data recorded included animal identification, rectal temperature, lung score, and antibiotic therapy at first treatment. Treatment outcome data were recorded by feed yard personnel utilizing an animal health computer. The outcome data tracked for this study included subsequent BRDC treatment or death of the animal. Our findings indicated that as lung auscultation score (P < .0001) or rectal temperature (P < .0001) increased there was an increased risk for cattle to require a second BRDC treatment. Also, we observed an increased risk for death loss in cattle with higher lung auscultation scores (P < .0001) or higher rectal temperature (P < .0001) at the time of treatment for BRDC. We have demonstrated that lung auscultation score and rectal temperature can be used as tools to predict treatment outcome in cattle treated for BRDC. Future research with these tools could be used to develop more precise therapeutic protocols for BRDC in feeder cattle.
Keywords: feedyard; auscultation; BRD; bovine; thoracic; lung; Agriculture, Animal Pathology (0476); Agriculture, General (0473); Biology, Animal Physiology (0433); Biology, Veterinary Science (0778); Health Sciences, Pathology (0571)